Financing Mechanisms for Addressing Remediation of Site Contamination - World Bank Group (World Bank, Washington, DC, 2015)
Industrial and commercial facilities provide great economic benefit to communities throughout the world. Unfortunately, many industries use or have used practices and materials which have proven toxic to the environment and to those who live and work near contaminated sites. The definition and degree of contamination varies at national and regional levels of government, but leaders throughout the world now recognize the hazard that contaminated industrial and service sites present to the wellbeing of their communities and seek innovative ways to finance the remediation of these challenging sites. Industrial contamination can have a severe, direct impact on adjacent communities. The cleanup and redevelopment of a so-called brownfield can improve a community s economy, provide an opportunity for habitat restoration, and create public space. Cleanup and redevelopment of brownfields can be an effective economic development strategy, with benefits seen in two timeframes. First, there is an immediate and one-time capital expenditure for cleanup activities, infrastructure, and construction. The initial investment generates tax revenues, temporary family-wage jobs, and indirect economic benefits within the community. Secondly, there is a long-term economic impact from remediation projects in the form of higher property values, long-term tax revenues, and the attraction of external capital to the community by tenants of the revitalized property. The economic benefit of contaminated site redevelopment is perhaps most clearly illustrated by permanent job creation from the restored properties. The deleterious effects of industrial contamination across all facets of a community typically provide a strong incentive for leaders to seek financing mechanisms that make site remediation possible.